Hongye Fan: A Pioneer in the Historical Studies of Science in Modern China. Issue 3 (3rd July 2021) - Wang, Zuoyue; Xiong, Weimin
Abstract: Professor Hongye Fan 樊洪业 (1942-2020) was a distinguished historian, scholar, and editor in the Chinese Academy of Sciences (CAS) in Beijing who helped lay the foundation for the historical studies of science in modern China with his writings, editing work on primary sources, and organizational efforts. Trained in biology he published historical studies on a wide-range of topics, including Jesuit missionaries in China, the May Fourth movement, Science Society of China, Lysenkoism, and the CAS. His major editorial achievements included the journal Yuanshi ziliao yu yanjiu 院史资料与研究 ( Materials and Studies on CAS History ), the 24-volume Zhu Kezhen quanji 竺可桢全集 ( The Complete Works of Coching Chu ), a 54-volume Chinese scientists' oral histories book series, and a national project to document the lives and careers of senior Chinese scientists. He also mentored a new generation of historians of science in modern China.